Penyuluhan dan Perbaikan Sarana Perlindungan Penampungan Air Di Kecamatan Selemadeg Timur Kabupaten Tabanan Tahun 2018 - I Wayan Sali; I Ketut Aryana; I Wayan Suarta Asmara; Anisyah Elly Yulianti (Jurnal Pengabmas Masyarakat Sehat, 2019)
Water is a basic human need that is used as a human survival instrument. Water is used for drinking, preparing daily meals, cleaning the body and household appliances, as well as environmental management. The use of water is very influential on public health because in the development of many water sources are polluted.This community service aims to increase public understanding about the quality of clean water in the protection of Batur river water reservoirs in Munduk Pakel Hamlet Gunung Sari Village, Selemadeg Timur District, Tabanan Regency and help improve the protection of their water reservoirs.The method used in this community service is inspection of river water storage protection, health counseling (discussion), improvement of protection of water reservoirs, and water quality inspection.The results of the sanitation inspection survey, the protection of the Munduk Batur river water storage in the Munduk Pakel Hamlet, Gunung Sari Village, was included in the risk of high pollution. As a result of discussions with the Village Head, the Head of the Munduk Pakel Hamlet and the Water Manager agreed to improve the Protection of Water Reservoir by making reinforced concrete cover, installation of pralon pipes, water quality checks for pH, temperature, coliform and E.coli parameters. From the laboratory results of Coliform and E. Coli all do not meet the requirements for drinking water and must be processed first by cooking until boiling. Counseling for households / people who drink, brush their teeth from the water to protect water reservoirs directly.It is expected that the public must always pay attention to the protection requirements of water storage and cooking water before drinking as well as to the Selemadeg Timur I Pukesmas to always make efforts to increase public knowledge about the use of water sources by providing counseling about water sources and water treatment properly, so can shape the attitude of the community better and later can practice it, so that environmental-based diseases can be suppressed.Keywords: Water protection, Water quality